Constructing a Digital Certificate Authentication System for Classified Documents - Shaker, Saif Ahmed; Nasir, Ayad Ghazi; Ali, Faez Hassan (Iraqi Journal of Science, 2023)
In this paper, we introduce a new digital authentication certification system to keep the classified documents' information safe. The proposed system is a steganography system divided into two subsystems, the first subsystem is responsible for embedding the information about the person, and it works in the main foundation that issues the documents, while the second subsystem is found in the beneficiary directorates to extract the true information of the person.